Mean Platelet Volume as a Predictor for Restenosis After Carotid Angioplasty and Stenting. Issue 4 (April 2018) - Dai, Zhengze; Gao, Jie; Li, Shun; Li, Rongrong; Chen, Zhaoyao; Liang, Meng; Liu, Xinfeng; Xu, Gelin
Abstract : Background and Purpose—: Platelet aggregation plays a vital role in the development of in-stent restenosis (ISR) after carotid angioplasty and stenting (CAS). Mean platelet volume (MPV) has been suggested as an index of platelet reactivity. This study aimed to investigate the association between MPV and ISR in CAS patients. Methods—: A total of 261 patients with CAS were enrolled. MPV was measured before CAS procedure. Digital subtraction angiography, computed tomographic angiography, or duplex ultrasonography was performed at 6 months and annually after the procedure. ISR was defined as ≥50% stenosis in the treated lesion. Cox regression was used to identify predictors of ISR after CAS. Results—: Of the 261 patients with CAS, 46 (17.6%) were determined with ISR during a mean follow-up of 12.1±16.1 months (range, 2.1–120.7). On multivariate analysis, baseline MPV >10.1 fL (hazard ratio, 3.20; 95% confidence interval, 1.28–8.03), lesion length (hazard ratio, 1.05; 95% confidence interval, 1.02–1.08), residual stenosis (hazard ratio, 1.07; 95% confidence interval, 1.05–1.10), and baseline glucose (hazard ratio, 1.01; 95% confidence interval, 1.00–1.02) were associated with ISR. Conclusions—: Elevated MPV may be associated with ISR after CAS. Patients with high preprocedural MPV may benefit from an intensified antiplatelet therapy after CAS. Abstract : Supplemental Digital Content is available in the text.